Computational Studies of Beta Amyloid (Aβ42) with p75NTR Receptor: A Novel Therapeutic Target in Alzheimer's Disease. (11th November 2014) - Devarajan, Shine; Sharmila, Jeya Sundara
Abstract : Alzheimer's disease is a neurodegenerative disorder characterized by the accumulation of beta amyloid plaques (A β ) which can induce neurite degeneration and progressive dementia. It has been identified that neuronal apoptosis is induced by binding of A β 42 to pan neurotrophin receptor (p75NTR) and gave the possibility that beta amyloid oligomer is a ligand for p75NTR. However, the atomic contact point responsible for molecular interactions and conformational changes of the protein upon binding was not studied in detail. In view of this, we conducted a molecular docking and simulation study to investigate the binding behaviour of A β 42 monomer with p75NTR ectodomain. Furthermore, we proposed a p75NTR-ectodomain-A β 42 complex model. Our data revealed that, A β 42 specifically recognizes CRD1 and CRD2 domains of the receptor and formed a "cap" like structure at the N-terminal of receptor which is stabilized by a network of hydrogen bonds. These findings are supported by molecular dynamics simulation that A β 42 showed distinct structural alterations at N- and C-terminal regions due to the influence of the receptor binding site. Overall, the present study gives more structural insight on the molecular interactions of beta amyloid protein involved in the activation of p75NTR receptor.